Tunja our natural home: a commitment of all for all (Revista de Diavulgación L'esprit Ingénieux, 2024)
AbstractThe initiative “Tunja Nuestro Hogar Natural” is part of a set of projects supported by the Santo Tomás University - Tunja, within the framework of the social projection and social support of the communities. In this sense, Tunja Nuestro Hogar Natural is focused on raising awareness in communities including environment, pollution, ecosystems, water resources and the greenhouse effect, which is influenced by above mentioned factors. The project seeks to go to vulnerable communities in the city of Tunja, where youth learning campaigns are not daily, so using talks, videos and educational activities for students, personal and social commitments help to people on how take care our environment. On the other hand, three different surveys were conducted to obtain information on the main community daily activities. The campaign was carried out in the first semester of 2020 at the Gonzalo Suárez Rendón High School in the city of Tunja. It was carried out by ten students from the Universidad Santo Tomás - Tunja, supervised by the professor Teresa Espitia and directed to approximately 300 students from fourth and fifth year. Finally, a socialization was conducted with the community where the students presented their points of view on the issues and the environmental commitments that they assume with the planet.
Keywords: environment, pollution, ecosystems, education.; environment, pollution, ecosystems, education